Pengelolaan Pembelajaran Pendidikan Agama Islam Di SMK Muhammadiyah Kartasura Kabupaten Sukoharjo Tahun Pelajaran 2015 - Syahril, Muhammad, Dr. Samino, M.M, Dr. Eko Supriyanto, S.H, M.H (2015)
Teaching learning process in the class is found the student attitude dan behaviour which could disturb on teaching learning process itself. It could influence the success of learning process and student achievement. To prevent the student behaviours which disturb of teaching learning process, the teacher tried to use class potential, focused on the students, understanding them individually, and given the certain services in the form of support from the school members. This research is about planning in Islamic Religious Education learning, Application of Islamic Religious Education learning and Evaluation of Islamic Religious Education learning in SMK Muhammadiyah Kartasura Sukoharjo to increase the student achievement. The result of research related to the planning of Islamic Religious Education learning. Planning is the begining process of learning to determine the purpose or objective that would be reached, so it could produce the efficient and effective learning. The steps that must be prepared in this learning are ; the analysis of effective day and learning program, making the yearly program, semester and claim program, arranging the syllabus, arranging of learning-planning, and scoring of learning. Application of Islamic Religious Education, the teachers have the responsibility in the process of teaching-learning process. It means the phisical environtment and situation of learning in the class. The good organized class which managed effectively and efficiently is essential foundation for doing a good instructional program and making the recpect care situation among the students and teacher. The evaluation learning result of Islamic Religious Education which is done by all teachers , especially PAI has been appropriate with the evaluation of learning result in KTSP, that is KTSP, it means scoring base on the class in the term of cognitif, physichomotoric, and affective. Key words: Planning; application; evaluation.